1999
DOI: 10.1111/j.1349-7006.1999.tb00742.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible Chemopreventive Effects of Bovine Lactoferrin on Esophagus and Lung Carcinogenesis in the Rat

Abstract: A milk component, bovine lactoferrin (bLF), previously shown by us to be a strong chemopreventive of colon carcinoma development, was examined for its influence on other organs using a rat multi-organ carcinogenesis model. Male F344 rats, aged 6 weeks, were treated sequentially with diethylnitrosamine (DEN, i.p.), dihydroxy-di-N-propylnitrosamine (DHPN, in drinking water) and N-nitrosomethylbenzylamine (NMBA, s.c.) during the first 8 weeks (DDN treatment), and then bLF was administered in the basal diet, at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 18 publications
1
52
0
Order By: Relevance
“…[17][18][19][20] Interestingly, in experimental studies, lactoferrin has been shown to inhibit the growth of some solid tumors such as colon, esophagus, and lung tumors. 21,22 Interestingly, stool lactoferrin has been shown to be a sensitive marker of intestinal inflammation in patients with intestinal tract symptoms and is being used in clinical practice to identify patients with intestinal tract inflammation. 23 Our results suggest that the detection of lactoferrin protein levels in the stool might also be a practical noninvasive screening test for pancreatic inflammation or cancer invasion among patients with suspected pancreatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] Interestingly, in experimental studies, lactoferrin has been shown to inhibit the growth of some solid tumors such as colon, esophagus, and lung tumors. 21,22 Interestingly, stool lactoferrin has been shown to be a sensitive marker of intestinal inflammation in patients with intestinal tract symptoms and is being used in clinical practice to identify patients with intestinal tract inflammation. 23 Our results suggest that the detection of lactoferrin protein levels in the stool might also be a practical noninvasive screening test for pancreatic inflammation or cancer invasion among patients with suspected pancreatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Lfn-p induces apoptotic cell death in the human oral squamous cell carcinoma cell line SAS Lfn and a pepsin-digested lactoferrin peptide, Lfc, have been reported to inhibit tumor cell growth and induce cell death (7,8). We examined whether Lfn-p induces cell death in the oral squamous cell carcinoma cell line SAS.…”
Section: Resultsmentioning
confidence: 99%
“…Lfc B from bovine Lfn induces cell death in a human leukemia cell line and in endocervix adenocarcinomas and breast cancers (7,8). Lfn is progressively down-regulated in neoplastic transformation (32).…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Among them, the anti-bacterial action of LF is considered to be caused through sequestra-tion of iron required for microbial growth. 24) Recently, chemopreventive ability of bovine LF (bLF) was demonstrated in chemically induced carcinogenesis in colon, [25][26][27] esophagus 28) and lung. 28) bLF could also inhibit intestinal polyposis in Apc Min mice.…”
mentioning
confidence: 99%
“…24) Recently, chemopreventive ability of bovine LF (bLF) was demonstrated in chemically induced carcinogenesis in colon, [25][26][27] esophagus 28) and lung. 28) bLF could also inhibit intestinal polyposis in Apc Min mice. 29) Moreover, bLF could inhibit tumor metastasis.…”
mentioning
confidence: 99%